ENTREPRENEURSHIP DAN PERLINDUNGAN ANAK - Nurliana Cipta Apsari; Meilanny Budiarti Santoso; Sahadi Humaedi; Santoso Tri Raharjo; Budhi Wibhawa (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2017)
ABSTRACT The rights of children from poor family and geographically unfortunate is violated due to limited access. Assisting families to overcome the access limitation by entrepreneurship is an effort for child protection. The study was conducted at Genteng Village to families with children between 0-18 years old using qualitative methode with in-depth interview technique. The result shows that geographically, the village is located in remote area with limited and unsmooth rocky road. The number of children in the village is high, however the education facilities are not sufficient. The majority of the parents work as farmers which the daily expenses are often greater than the income. These conditions made the children in the village vulnerable of receiving social injustice thus entrepreneurship can be endorsed in addressing poverty in the area. The entrepreneurship potential in the village such as cooperation and various farmers group are supported to enhance the earner of the members to decrease the poor family thus the children can escape from the poverty. Keywords: Entrepreneurship, child protection, social justice ABSTRAK Anak dari keluarga miskin dan secara geografis terisolasi mendapatkan ketidakadilan sosial karena keterbatasan akses. Mendekatkan akses atau membantu mengurangi kesenjangan yang dialami keluarga dengan kegiatan kewirausahaan adalah usaha perlindungan anak. Penelitian dilakukan di Desa Genteng kepada orang tua dengan anak usia 0-18 tahun dengan menggunakan metode kualitatif dengan teknik wawancara mendalam. Hasil penelitian menemukan lokasi geografis jauh dari pusat keramaian dengan jalan berkelok dan berbatu. Jumlah anak cukup tinggi, namun fasilitas pendidikan minim. Orang tua mayoritas bertani dengan pengeluaran cenderung lebih banyak daripada pendapatan. Keadaan ini membuat anak di Desa Genteng rawan mendapatkan ketidakadilan sosial, sehingga kewirausahaan menjadi cara mengatasi kemiskinan. Potensi kewirausahaan seperti koperasi, dan kelompok tani teridentifikasi dapat meningkatkan pendapatan di Desa Genteng, sehingga anak-anak dapat terlepas dari rantai kemiskinan. Kata kunci: Kewirausahaan, perlindungan anak, keadilan sosial